Influence of coupling agent and fibre treatment to mechanical properties of oil palm fibre reinforced polymer matrix composite / Muhamad Fitri and Shahruddin Mahzan - Fitri, Muhamad; Mahzan, Shahruddin (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
This research investigates the effect of alkali treatment and the coupling agent to the mechanical properties of oil palm reinforced polymer composites. The polypropylene was used as the reinforcement matrix whereas the oil palm fibres were used as the reinforcement fibres. The oil palm fibres were prepared in two conditions namely alkali treated and untreated fibres. During the composite material preparation, the untreated fibres were prepared in two conditions; i.e. without coupling agent and with coupling agent. Here, the coupling agent used was the Polypropylene grafted Maleic Anhydride (PPgMA). The fibres were determined at 10% for all specimens. All specimens were mechanically tested for Charpy impact and tensile tests. The results show that the impact strength and the ultimate tensile strength were not influenced by the alkali treatment. However, alkali treatment significantly increases both strain percentages at the ultimate tensile and at the break points. It was also observed that by adding the coupling agent, the impact strength and the strain percentage at ultimate tensile and break points were improved significantly. However, the tensile strength of the specimens were not influenced by the coupling effect. This finding was essential in determining the influence of coupling agents in polymer matrix composite strength.